Stimulation of superoxide production increases fungicidal action of miconazole against Candida albicans biofilms - De Cremer, Kaat (Sci Rep, 2016)
We performed a whole-transcriptome analysis of miconazole-treated Candida albicans biofilms, using RNA-sequencing. Our aim was to identify molecular pathways employed by biofilm cells of this pathogen to resist action of the commonly used antifungal miconazole. As expected, genes involved in sterol biosynthesis and genes encoding drug efflux pumps were highly induced in biofilm cells upon miconazole treatment. Other processes were affected as well, including the electron transport chain (ETC), of which eight components were transcriptionally downregulated. Within a diverse set of 17 inhibitors/inducers of the transcriptionally affected pathways, the ETC inhibitors acted most synergistically with miconazole against C. albicans biofilm cells. Synergy was not observed for planktonically growing C. albicans cultures or when biofilms were treated in oxygen-deprived conditions, pointing to a biofilm-specific oxygen-dependent tolerance mechanism. In line, a correlation between miconazole’s fungicidal action against C. albicans biofilm cells and the levels of superoxide radicals was observed, and confirmed both genetically and pharmacologically using a triple superoxide dismutase mutant and a superoxide dismutase inhibitor N-N′-diethyldithiocarbamate, respectively. Consequently, ETC inhibitors that result in mitochondrial dysfunction and affect production of reactive oxygen species can increase miconazole’s fungicidal activity against C. albicans biofilm cells.